Genetic resources in beans, Phaseolus vulgaris, and CIAT`s germplasm bank - Burns, R. (International Center for Tropical Agriculture, 1975)
The availability of genetic variation in beans in the world is analyzed, emphasizing the activities and objectives of CIAT`s bean germplasm bank. A list of the institutions with bean collections is included with emphasis on the need for new explorations and collections. Factors affecting the multiplication, evaluation, and documentation of the existing collections are analyzed. CIAT`s germplasm bank and its manner of operation are briefly described; a list of agronomic characteristics evaluated on each entry to the bank is included. (CIAT)